Language as a lightning rod: Power contests, emotion regulation, and subgroup dynamics in global teams - Hinds, Pamela J; Neeley, Tsedal B; Cramton, Catherine Durnell (Journal of International Business Studies, 2014)
Based on an ethnographic study comprising interviews with and observations of 96 globally distributed members of six software development teams, we propose a model that captures how asymmetries in language fluency contribute to an us vs them dynamic common in global teams. Faultlines, formed along the dimensions of asymmetries in lingua franca fluency, location, and nationality of team members, were associated with subgrouping in some but not all of the teams. Our findings suggest that divisive subgroup dynamics occurred only in teams that also suffered from power contests, suggesting that power contests activate otherwise dormant faultlines. Our findings extend theory on subgroup dynamics in global teams by adding language as a potential faultline dimension, showing how power struggles activated faultlines and were, in turn, reinforced by them and documenting the emotion-regulation processes triggered by subgrouping and enacted through language-related choices and behaviors.